Synthesis Optimization and Extraction of Rare Earth Metal Ions by Poly (N - Methylhydroxamic Acid) Resin - Balci, Seckin (1998)
Poly(N-methyl hydroxamic acid) resin was synthesized from crosslinked poly(methacrylate-divinyl benzene). The optimum amounts of N- metylhydroxylam ine hydrochloride, NaOH, poly(methacrylate) were 2.2g, 4g and and 4 g, respectively and 20 ml water-ethanol solution (75%) was used. The reaction was completed at room temperature, for 24 hours. The abilities of poly(Nm ethylhydroxamic acid) resin and poly(N-unsubstituted hydroxamic acid) resin to form complexes with Cu ion were compared. Kinetics study carried out indicated that metal sorption process by the resin is fast and it is suitable to be used in column technique. The resin showed good stability in buffer pH 4 and 1 MHCI solution . Metal sorption capacities were determined for Cu, Fe, Y, La, Ce, Sm , Vb, Nd, Pr, Dy and Gd. Separations of Cu / Fe, Y / Sm , Y / Nd, Sm / La have been carried out.